Adverse clinical events in Japanese atrial fibrillation patients with and without coronary artery disease—findings from the SAKURA AF Registry. (2nd December 2019) - Fukamachi, Daisuke; Okumura, Yasuo; Yokoyama, Katsuaki; Matsumoto, Naoya; Tachibana, Eizo; Kuronuma, Keiichiro; Oiwa, Koji; Matsumoto, Michiaki; Nishida, Toshihiko; Kojima, Toshiaki; Hanada, Shoji; Nomoto, Kazumiki; et al.
Abstract: Background: Although atrial fibrillation (AF) and coronary artery disease (CAD) are increasing in prevalence in Japan, real-world data regarding clinical outcomes in Japanese AF patients with CAD are limited. Methods: The SAKURA AF Registry is a prospective multi-center registry created to investigate outcomes of oral anticoagulant (OAC) use in Japanese AF patients. A study was conducted involving 3237 enrollees from 63 Tokyo-area institutions who were followed up for a median of 39.3 months. Clinical adverse events were compared between the patients accompanied with ( n = 312) and without CAD ( n = 2925). Results: The incidence of cardiovascular events and all-cause mortality rates were significantly higher among patients with CAD than among those without CAD (5.98 vs 2.52 events per 100 patient-years, respectively, p < 0.001; 3.27 vs 1.94 deaths per 100 patient-years, respectively, p = 0.012), but there was no difference in strokes/transient ischemic attacks or systemic embolisms (1.70 vs 1.34). After a multivariate adjustment, CAD remained a risk factor for cardiovascular events (hazard ratio [HR] = 1.57, 95% confidence interval [CI] = 1.08–2.25, p = 0.018). Among CAD patients, the propensity score-adjusted risk for major bleeding was significantly decreased among direct oral anticoagulant (DOAC) users in comparison to that among warfarin users (HR = 0.29, 95% CI = 0.07–0.94, p = 0.04), but other adverse clinical events did not differ significantly between these two groups. Conclusions: CAD did not appear to be a major determinant of strokes/TIAs, major bleeding, or all-cause mortality, but appeared to increase the risk of cardiovascular events in Japanese AF patients. The risk of major bleeding in CAD patients appeared to decrease when a DOAC rather than warfarin was administered. The data suggested that patients with AF and concomitant CAD require careful management and follow-up to reduce cardiovascular risks, and DOACs may be a better choice over warfarin when considering the risk of major bleeding.